Case Report on Thiazide-induced Hyponatremia Leading to Extra Pontine Myelinolysis - Unnisa, Habeeb; Anusha, Manda; Mandava, Kiranmai; Anusha, Are (Indian Journal of Pharmacy Practice)
Extra Pontine Myelinolysis (EPM) is a type of neurological disorder characterized by altered sensorium, movement abnormalities, seizures, and parkinsonian-like symptoms. It is a rare disorder involving wide etiological factors of which the most common is hyponatremia and its correction. Hyponatremia usually develops as a result of the use of certain medications like benzodiazepines, diuretics, etc. other causes include chronic kidney disease, heart disease, and metabolic disorders. EPM can be diagnosed with MRI and CT scans. In order to prevent this fatal disease, it is recommended to closely monitor the patients on medication like thiazides or benzodiazepines for serum sodium levels and maintain adequate amounts with adjuvant therapies and follow recent guidelines for the controlled correction of existing hyponatremia. Myelinolysis can only be treated symptomatically with neurological agents and physical therapies as no specific cure exists.
Keywords: Extra pontine myelinolysis; Hyponatremia; Benzodiazepines